Analisis Pengaruh Kompetensi terhadap Kinerja Perawat Puskesmas di Kabupaten XYZ Sumatera Barat - Rike Gussanti Handayani Nasution; Rahmi Fahmy; Emil Huriani (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The nurse's performance in providing nursing care has not been implemented well. This study aims to analyze and identify the influence of competency on the performance of nurses in the health center in Dharmasraya District. This type of research is descriptive correlation with cross sectional approach. The population of this study was all nurses at the health center in Dharmasraya District, with a sample of 165 nurses, using proportional random sampling. The data analysis method used was SEM with the help of Smart-PLS. Based on the results of testing the hypotheses obtained three variables that have a significant positive influence on the performance of the health center nurses, namely helping role competency, therapeutic interventions and work roles on the performance of the health center nurses. For the teaching-coaching variable there is no positive but significant influence on the performance of the health center nurse. In the diagnostic function competency, managing situation and ensuring quality does not have a significant positive effect on the performance of the health center nurse. It is expected that the organization can maintain three competencies that affect the performance of nurses and improve competencies that are still lacking through training, seminars and supervision.